Production and Evaluation of Breakfast Cereals from Flour Blends of Maize (Zea mays) and Jackfruit (Artocarpus heterophyllus Lam.) Seeds - , Nkiru E. Odimegwu; , Chigozie E. Ofoedu; , Gloria C. Omeire; , Munachiso C. Umelo; , Chioma N. Eluchie; , Serah O. Alagbaoso; , Njideka E. Njoku; , Peace O. Ozoani (Archives of Current Research International, 2019)
Aim: Jackfruit is an underutilized tropical and subtropical fruit that is consistently lost to wastages and postharvest losses, neither has it gained substantial research attention. Therefore, the study is aimed at the production and evaluation of breakfast cereals formulated from composite blends of maize flour and jackfruit seed flour. Study Design: This study was made to fit into a one way Analysis of Variance. Place and Duration of Study: The research was carried out at the Department of Food Science and Technology laboratory, Federal University of Technology, Owerri, Nigeria, between February 2018 and October 2018. Methodology: Flaked breakfast cereals were produced from blends of different ratios of Maize flour to Jackfruit seed flour. The formulated breakfast cereal products were evaluated for proximate composition, functional properties, anti-nutritional properties, mineral content and sensory properties. Results: The mineral content of the formulated breakfast cereals showed significant difference (P<0.05) in Ca(156.23-184.14mg/100g), Mg (179.28-207.81mg/100g), K(70.62-78.53mg/100g), Fe(4.01-5.46mg/100g), Na(9.44-10.66mg/100g), Zn(1.72-2.29mg/100g) and P(10.38-13.62mg/100g). The moisture content (3.83 - 4.14%) of the formulated products was acceptable for shelf life extension of the flaked breakfast cereal products. Protein, ash, crude fiber and fat content of the formulated breakfast cereal products increased with increased addition of jackfruit seed flour while the carbohydrate and energy value of the formulated products decreased with increased addition of jackfruit seed flour. Bulk density and water absorption capacity of the formulated products increased with increased addition of jackfruit seed flour while oil absorption capacity, foam capacity, viscosity and gelation capacity decreased with increased addition of jackfruit seed flour. Processing method significantly reduced the relatively high level of anti-nutrients associated with Jackfruit seed. Panelist preference increased with a corresponding decrease in jackfruit seed flour addition. Conclusion: Utilization of jackfruit in food product development may solve the problem of wastage and postharvest losses associated with this fruit.